Enough Already! : A Socialist Feminist Response to the Re-emergence of Right Wing Populism and Fascism in Media (2020)
This text will explore the re-assertion of right-wing populist and fascist movements as presented and distributed in the media. In particular, attacks on immigrants, women, minorities, LGBTQ people are increasing at a frightening rate, along with the election of politicians who openly support authoritarian discourse and scapegoating. More troubling is how this discourse is inscribed into laws and policies. However, despite the urgency of the situation, what we call “the Left” has so far been unable to definitively respond to these events, whether it is a matter of liberals insisting on hands-off free speech policies, including covering “both sides of the issue” no matter how absurd, or socialists who utilize a tunnel vision focus on economic issues at the expense of women and minorities. In order to effectively resist right-wing movements of this magnitude, a socialist/Marxist feminist analysis is necessary for understanding how racism, sexism, and homophobia are conduits for capitalism, not just ‘identity issues.’